Nanomaterials to combat SARS-CoV-2: Strategies to prevent, diagnose and treat COVID-19 - Valenzuela-Fernández, Agustín; Cabrera-Rodriguez, Romina; Ciuffreda, Laura; Perez-Yanes, Silvia; Estevez-Herrera, Judith; González-Montelongo, Rafaela; Alcoba-Florez, Julia; Trujillo-González, Rodrigo; García-Martínez de Artola, Diego; Gil-Campesino, Helena; Díez-Gil, Oscar; Lorenzo-Salazar, José M.; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the associated coronavirus disease 2019 (COVID-19), which severely affect the respiratory system and several organs and tissues, and may lead to death, have shown how science can respond when challenged by a global emergency, offering as a response a myriad of rapid technological developments. Development of vaccines at lightning speed is one of them. SARS-CoV-2 outbreaks have stressed healthcare systems, questioning patients care by using standard non-adapted therapies and diagnostic tools. In this scenario, nanotechnology has offered new tools, techniques and opportunities for prevention, for rapid, accurate and sensitive diagnosis and treatment of COVID‐19. In this review, we focus on the nanotechnological applications and nano‐based materials (i.e., personal protective equipment) to combat SARS-CoV-2 transmission, infection, organ damage and for the development of new tools for virosurveillance, diagnose and immune protection by mRNA and other nano-based vaccines. All the nano-based developed tools have allowed a historical, unprecedented, real time epidemiological surveillance and diagnosis of SARS-CoV-2 infection, at community and international levels. The nano-based technology has help to predict and detect how this Sarbecovirus is mutating and the severity of the associated COVID-19 disease, thereby assisting the administration and public health services to make decisions and measures for preparedness against the emerging variants of SARS-CoV-2 and severe or lethal COVID-19.